(untitled) (Journal of Student Affairs in Africa, 2021)
This article stemmed from discussions related to residence committee members and their role as leaders within their communities. The ideas presented during these conversations gave rise to a research interest for a conceptual exploration of collaborative and progressive social transformative brokering within a complex context. In particular, the identified interest within this context relates to finding common ground, between, inter alia, student affairs management, and residence committee (RC) management in residence spaces. The specific focus is the RC leadership team as strategists who are positioned to deal with potential conflict resolution in policy interpretation and enactment. The argument presented here has to do with the extent to which they can do this in a manner that facilitates the collegial and amicable interpretation of policy in residence communities. Inherent within this is the notion of managing the potential disjuncture between policy formulation and policy implementation. The primary question about this concern finds expression in how RCs move from being part of active cultural residence spaces to critical participants in dialogic conversations as part of a multi-perspectival progressive transformation strategy. Indeed, while bringing about transformation, the dynamic issues of brokering cohesion within a context of ideological and political complexity remain. Given the inherent situational complexities, the article adopts a bricoleuric theoretical thread that requires a multiperspectival orientation. In this regard, appropriate components of critical complexity theory, critical system theories, transformative learning, and hope theory account for this theoretical approach. A further consideration is that of a positionality of finding progressive and transformative common ground. In this regard, the argument revolves around examining the systemic factors that bear relevance for actualising the envisaged intention, that is, common ground in the interests of the common good. At stake in this argument is the notion of RC identity and their role in building a values-based residence system of policy interpretation and enactment, while bridging the ideological divide and finding common ground between the expectations of student affairs management and the residence community.